The Conceptual Framework for 360 Degree Feedback: Objectives, Requirements, and Conditions for Success - Iman Mohammed Zaid Al-Maawali; Tengku Sarina Aini Binti Tengku Kasim; Asyraf Isyraqi Bin Jamil (Taez University, 2024)
360-degree feedback is the process of collecting and measuring co-worker feedback from multiple sources. The descriptive objectives of this study to discussed the conceptual framework of the 360-degree feedback method, which is part of an extensive study conducted by the researcher. Objectives: presenting the concept of the feedback method, defining the objectives of the method, discussing the reasons for use, the advantages and disadvantages of the method, application requirements, and finally the conditions for the success of the feedback (360) degrees. The study adopted the descriptive analytical approach, and the method of collecting quantitative. The results showed that the objectives of the method are useful for work and career development, including self-development, leadership development, management and implementation development, identifying the training needs of employees, reducing traditional performance appraisal errors, and introducing the individual to his or her level of performance. As for the reasons that led to the use of the method, they are: the transformation of companies from hierarchical organization to horizontal organization, widening the scope of supervision, obtaining broader points of view, improving the school climate based on justice. Among the advantages are for revealing the gap between the individual's perspective in evaluating his or her performance, and the perspective of others for this performance, building training programs for employees, enhancing the orientation towards teamwork and exchanging experiences, helping to make decisions related to promotion and wage increase. As for the defects, they included: the possibility of being affected by various biases, such as the halo effect, the recency bias, the indulgence bias, in addition to the employees' reluctance to provide negative feedback even if it was honest, the delay in the feedback process, and low participation rates. The errors were limited to (13) errors that may occur when using this method. As for the requirements, they included: defining objectives, defining target individuals. Determine the method of analyzing the information, carrying out an awareness and communication campaign, and following up the implementation accurately. Among the conditions for the success of the assessment: that the feedback is done honestly in the light of specific objectives, adopt impartiality, objectivity, scientific and professional properly. Focus on the performance, not the person. Taking into account the feelings of workers when providing negative feedback. It should be comprehensive and provide positive and negative feedback. Share external sources.